1996
DOI: 10.1007/s004460050018
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous, asynchronous, and causally ordered communication

Abstract: This article studies characteristic properties of synchronous and asynchronous message communications in distributed systems. Based on the causality relation between events in computations with asynchronous communications, we characterize computations which are realizable with synchronous communications, which respect causal order, or where messages between two processes are always received in the order sent. It is shown that the corresponding computation classes form a strict hierarchy. Furthermore, an axioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 40 publications
(32 reference statements)
0
47
0
Order By: Relevance
“…In a classification of a hierarchy of communication patterns, Charron-Bost et al observed that a distributed algorithm designed to run correctly on asynchronous systems (called A-computations) may not run correctly on synchronous systems}an algorithm that runs on an asynchronous system may deadlock on a synchronous system [9]. A-computations that can be realized under synchronous communication are called realizable with synchronous communication (RSC) computations.…”
Section: The Crown Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a classification of a hierarchy of communication patterns, Charron-Bost et al observed that a distributed algorithm designed to run correctly on asynchronous systems (called A-computations) may not run correctly on synchronous systems}an algorithm that runs on an asynchronous system may deadlock on a synchronous system [9]. A-computations that can be realized under synchronous communication are called realizable with synchronous communication (RSC) computations.…”
Section: The Crown Criterionmentioning
confidence: 99%
“…The communication patterns identified in this framework are shown to be generalizations of those used in areas or problems such as: formulating the temporal interactions of intervals [13], synchronous and causally ordered communication [9], determining size of logical clocks [8,20], designing distributed implementations for multilevel secure replicated databases and hierarchically decomposed databases [1,2], ordering of concurrent events without synchronization [1], transfer of knowledge [7], concurrency measures [10], determining necessary and sufficient conditions for a consistent global state [6,19] which is useful in checkpointing and recovery [3][4][5], and defining distributed deadlocks [14]. Thus, the paper shows that key concepts and structures in areas such as the above are instantiations of the communication patterns identified in the presented framework.…”
Section: Introductionmentioning
confidence: 98%
“…Another synchronization constraint is related to message ordering [26]. Ensuring an order of message reception, like point-to-point FIFO, adds synchronization which can lead to a loss of efficiency and a gain in program properties.…”
Section: Dimensions Of Comparison Between Languagesmentioning
confidence: 99%
“…We adopt asynchronous message passing: send commands will not be blocked, while receives will be blocked if there is no message received on the designated ports. We assume the state of a port is a queue, and messages are transmitted following the FIFO-principle [3].…”
Section: Event Trace -The Basic Program State Settingsmentioning
confidence: 99%